The Political Role of The Icmi After The 1999 General Election: From Political Vehicle to An ‘Umbrella’ Organization - Imron Rosidi (Asia-Pacific Journal on Religion and Society, 2018)
After the fall of the New Order, ICMI as an organization of Indonesian Muslim Intellectuals established in the New Order era, which was originally close to the government party (Golkar), scattered to look for a more appropriate political channel. Diverse ideologies and backgrounds resulted in ICMI members establishing and joining different political parties. Although, there are still a number of other ICMI members remaining loyal to the Golkar party. However, the results of the 1999 elections disappointed a number of ICMI members who had joined in a number of these parties. The disappointment implies the birth of the "Central Axis" which is driven by Amien Rais. Therefore, it is true to say that ICMI in the New Order was very important because being a political vehicle turned into an 'association' organization which incidentally after the 1999 election encouraged the birth of the Central Axis.